(untitled) (Filologia e Linguística Portuguesa, 2023)
The present study aimed to contribute to the development of a quantitative approach to the analysis of editions, here called editometry, taking as object of study eight editions (1614, 1678, 1711, 1829, 1952-53, 2010, 1984 and 1998) of the sixteenth-century work Peregrinação, by Fernão Mendes Pinto, and specifically focusing on the conjectures made by the editors. It was tested the hypothesis that the progress of textual criticism in the 17th century (time of princeps edition) to the 21st century (present time) had an impact on the editions of Peregrinação in the form of a reduction in the practice of conjecture. It was confirmed the hypothesis, since the number of conjectures in the analyzed sample is greater in the initial edition, from 1678, than in the final edition, from 2010. It was found, however, that there is a mismatch between the patterns in which errors occur and those in which conjectures are made, with special reference to cases of error by omission/conjecture by addition and error/conjecture by substitution.